Generation of pulsed electron beams by simple cold cathode plasma guns - Wernsman, B., author; Rocca, Jorge J., author; Ranea-Sandoval, H. F., author; Mancini, H., author; IEEE, publisher (Colorado State University. Libraries, 1986)
Electron-beam pulses of current up to 20 A have been generated using glow discharge electron guns of simple construction. Beam pulses of 1-20 μs long at energies between 2 and 15 keV have been created at helium pressures between 1 and 5 torr. Results obtained using 3-cm diameter aluminum cathodes of two different geometries are discussed. As an example of the use of these electron guns for laser excitation, we have excited an He-Zn metal vapor mixture. Three new infrared laser transitions in ZnII are reported.